Waste ceramic powder incorporated alkali activated mortars exposed to elevated Temperatures: Performance evaluation. (30th October 2018) - Huseien, Ghasan Fahim; Sam, Abdul Rahman Mohd; Mirza, Jahangir; Tahir, Mahmood Md.; Asaad, Mohammad Ali; Ismail, Mohammad; Shah, Kwok Wei
Highlights: High volume waste ceramic powder incorporated AAMs were prepared and characterized. Performance of such AAMs were assessed under elevated temperature exposure. Microstructure of AAMs were sensitive to the variation of WCP contents. Abstract: This paper reports the effects of high volume waste ceramic powder (WCP) inclusion on the mechanical and microstructure properties of alkali activated mortars (AAMs) exposed to elevated temperatures. Such ternary mixes were designed by blending the abandoned waste materials from Malaysian agro and construction industries including WCP, ground blast furnace slag (GBFS), and fly ash (FA) with low concentration of alkaline activators. The as-prepared mortar specimens were heated up to 900 °C to determine their temperature dependent residual compressive strength, weight loss, and microstructures. The deterioration of the AAMs at elevated temperatures was evaluated by X-ray diffraction measurement, thermo-gravimetry analyser (TGA), Fourier transformed infrared (FTIR) spectroscopy, and field emission scanning electron microscopy (FESEM). The resistance of the proposed AAMs to elevated temperatures was enhanced with the increase WCP contents from 50 to 70%. Furthermore, the replacement of GBFS by FA in the ternary blends led to the reduction of the mortar deterioration up to 900 °C.